EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH NOMOR 2 TAHUN 2021 TENTANG PENATAAN TOKO MODERN DIKELURAHAN PANGKAJENE KABUPATEN SIDENRENG RAPPANG - Ramadhani, Nurul (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the effectiveness of the implementation of Regional Regulation No. 2 of 2021 concerning the Arrangement of Modern Stores in Pangkajenne Village, Sidenreng Rappang Regency. The background to this research is the increasing number of modern stores, which have the potential to displace traditional markets and small businesses. The local government has established regulations through regional regulations, but their implementation still faces various obstacles in the field. This study used a quantitative approach, using a questionnaire distributed to respondents in the Pangkajenne Village market area. The analysis used descriptive statistics and simple linear regression tests using SPSS. The results indicate that the implementation of the regional regulation has not been optimal. Some respondents assessed that implementation has been carried out according to the stages, but oversight is still considered weak. The target accuracy indicator has not been met because there are still modern stores located near traditional markets. Public satisfaction with this policy is also low because the benefits of the regulation have not been felt evenly, especially by traditional market traders. Overall, the effectiveness of Regional Regulation No. 2 of 2021 in Pangkajenne Village is considered ineffective. Improved supervision, coordination between parties, and outreach are needed to optimally achieve the goals of modern store arrangement.